An upper bound on the radius of a 3-edge-connected graph - Dankelmann, Peter; Mukwembi, Simon; Swart, Henda C. (Utilitas Mathematica, 2007)
Let G be a 3-edge-connected graph of order n and radius rad(G). Then the inequality rad(G) ≤ 1/3n + 17/3 is proved. Moreover, graphs are constructed to show that the bound is asymptotically sharp.